Water and bioenergy - a case study from the Thai ethanol sector - Amarasinghe, Upali A.; Damen, B.; Eriyagama, Nishadi; Soda, Wannipa; Smakhtin, Vladimir U. (2012)
Modern bioenergy systems are attracting increasing attention from governments in Asia as a potential solution to a range of policy problems related to energy security and sustainable development. Despite growing interest in bioenergy systems, there is still a limited understanding of how their expansion could impact on natural resources such as water. This paper aims to shed some light on the relationship between modern bioenergy development and water depletion using a case study on the biofuel sector in Thailand. This case study also includes an assessment of the impact of biofuel developments on water quality in water systems proximate to bioenergy production facilities in Thailand.